Is Bank Interest Ribâ? A Content Analysis - Murniati Mukhlisin (Journal of Islamic and South East Asian Finance and Accounting, 2023)
This research aims at analyzing the interpretation of ribâ in the current Islamic banking practices to find an answer if bank interest is ribâ. The methodology of this research is qualititative research that employs content analysis approach. The finding shows that there are three distinct groups emerging. The first group contends that bank interest constitutes ribâ, the second group asserts that it does not, and the third group attempts to navigate between the two banking systems. Given the ever-changing nature of time, place, and era, this study concludes that it is crucial for individuals to comprehend and implement Islamic contracts in their economic endeavors. This responsibility falls on academics, who should provide a simplified explanation of the language used in Islamic contracts, as the aforementioned language demands interpretative skills for comprehension. The public is guided by a fatwa from the MUI stating that bank interest is considered haram. Meanwhile, academics are urged to continually explore debates from diverse sources, including the perspectives of past scholars. According to the fiqh maxim, Al-Muhāfazah 'ala al-qadīm al-şālih wa al-Akhzu bil al-jadid al-aşlah it is recommended for all to uphold beneficial old traditions while embracing modern practices that align with Islamic values. This study is expected to make a contribution in terms of policy recommendation in affirming the ribâ understanding and Islamic banking practices in different jurisdictions.